A college girl's dietary experiment - Hanson, Ellen A. (My University, 1907)
Introduction: A dietary experiment extending through the month of April, 1907, was carried out by twelve senior Domestic science girls. The diet consisted of three regular meals per day, prepared by the girls according to a certain order. The supplies were all carefully weighed and an account kept of them. The girls were allowed to eat nothing outside of these supplies so that we might ascertain the exact amount of food consumed. This was made still more accurate by the weighing of all waste so that the exact amount of each food eaten was known. The diet consisted of meals well balanced and of food at a moderate cost. There were no other restrictions as to the diet, except that the food be well cooked and served on time. The object of the experiment was to ascertain the effect on the girls of a well cooked nourishing diet taken regularly, together with a moderate amount of exercise and plenty of sleep. The amount, cost, and caloric value of food used where no restrictions were enforced was another object of the experiment.
Citation: Hanson, Ellen A. A college girl's dietary experiment. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Dieting; Nutrition; Dieting Experiments; Theses